2019
DOI: 10.3390/plants8110518
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity for Drought, Heat and Combined Drought and Heat Stress Tolerance in Early Maturing Maize Landraces

Abstract: Climate change is expected to aggravate the effects of drought, heat and combined drought and heat stresses. An important step in developing ‘climate smart’ maize varieties is to identify germplasm with good levels of tolerance to the abiotic stresses. The primary objective of this study was to identify landraces with combined high yield potential and desirable secondary traits under drought, heat and combined drought and heat stresses. Thirty-three landraces from Burkina Faso (6), Ghana (6) and Togo (21), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 32 publications
13
49
0
1
Order By: Relevance
“…In agreement with previous studies [19], the wide range of variation in GY losses observed in this study indicated that indeed the applied stresses were severe and that the yield levels observed could be attributed to stress tolerance. Compared with the NS environment, HS, DS, and DSHS, on the averaged reduced GY by~23%, 49%, and 58%, respectively (Tables 1 and 2), suggesting that the effect of the combined stresses on GY of the extra-early maize accessions was higher than the individual effects but lower than their sum (hypo-additive effect).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with previous studies [19], the wide range of variation in GY losses observed in this study indicated that indeed the applied stresses were severe and that the yield levels observed could be attributed to stress tolerance. Compared with the NS environment, HS, DS, and DSHS, on the averaged reduced GY by~23%, 49%, and 58%, respectively (Tables 1 and 2), suggesting that the effect of the combined stresses on GY of the extra-early maize accessions was higher than the individual effects but lower than their sum (hypo-additive effect).…”
Section: Discussionsupporting
confidence: 93%
“…Compared with the NS environment, HS, DS, and DSHS, on the averaged reduced GY by~23%, 49%, and 58%, respectively (Tables 1 and 2), suggesting that the effect of the combined stresses on GY of the extra-early maize accessions was higher than the individual effects but lower than their sum (hypo-additive effect). These results corroborated the findings of earlier workers who reported higher yield losses from the combined effects of DS and HS than DS and HS applied alone in cereals including maize [17,19,29,46]. The high GY loss under DSHS compared to HS and DS could be attributed to the interaction effects of HS and DS on stomatal movements [46].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations